2003
DOI: 10.1001/archpsyc.60.9.993
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trajectories of Depression and Anxiety in a Prospective Community Study

Abstract: These findings have important implications for classification and treatment of affective disorders. The greater stability of comorbid anxiety and depression than either disorder alone illustrates the importance of further investigation of comorbid states compared with noncomorbid states in etiologic and treatment research. The persistence of subthreshold-level depression and anxiety from early to mid adulthood also suggests the importance of characterizing the continuum of expression of depression and anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
134
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(157 citation statements)
references
References 60 publications
18
134
0
1
Order By: Relevance
“…disorder alone, and particularly anxiety, is far lower than that of co-morbidity (Merikangas et al 2003).…”
Section: Coursementioning
confidence: 86%
“…disorder alone, and particularly anxiety, is far lower than that of co-morbidity (Merikangas et al 2003).…”
Section: Coursementioning
confidence: 86%
“…A significant comorbidity of substance use with affective disorder, especially bipolar disorder, and schizophrenia is well established (Kessler et al 2005;Marmorstein et al 2010;Merikangas et al 2003). More recently, comorbidity with anxiety disorders has emerged as a focus (Grant et al 2009).…”
Section: Definition Of Anxiety Disordersmentioning
confidence: 99%
“…The most prevalent comorbidities are anxiety disorders,8 substance use disorders9 and other depressive disorders. Epidemiologic studies have shown that the prevalence of at least one lifetime anxiety disorder was 59% in patients with lifetime MDD,10 while the prevalence of substance use disorders in MDD was 14% 9.…”
Section: Introductionmentioning
confidence: 99%